Technology and Sustainability in Integrated Transportation Hubs: A Systematic Literature Review - Darwisman, Samuel; Simanjuntak, Yosef Ricky (UI Scholars Hub, 2025)
Background: Integrated transportation hubs serve as a critical foundation for modern urban mobility, tasked with efficiently coordinating passenger and freight logistics flows. However, current research remains fragmented across disciplines, resulting in a lack of unified understanding regarding the synergy between advanced technology and holistic sustainability. Aims: This study aims to map the global research landscape of integrated transportation hubs to identify dominant themes, analyze the gap between technological potential and policy reality, and formulate a strategic future research agenda. Methods: Adhering to PRISMA 2020 guidelines, a systematic literature search was conducted across Scopus, Web of Science, and ScienceDirect databases up to July 2025. A double-blind screening process using Rayyan, quality appraisal via the CASP checklist, and thematic synthesis were applied to 25 high-impact review articles published between 2020 and 2025. Results: The analysis reveals four interconnected pillars: Technology and Digitalization; Holistic Sustainability; Logistics Integration; and Integrated Governance. Significant implementation barriers identified include institutional fragmentation, data interoperability challenges, and user behavioral inertia. Conclusion: Hub development transcends mere infrastructure projects, representing the creation of complex socio-technical ecosystems. Successful implementation necessitates synergizing technological innovation with adaptive governance and human-centric design to bridge prevailing policy gaps.